Adolescents with disabilities participate in the shopping mall: facilitators and barriers framed according to the ICF. Issue 21 (8th October 2016) - Dahan-Oliel, Noémi; Shikako-Thomas, Keiko; Mazer, Barbara; Majnemer, Annette
Abstract: Purpose: Community participation is restricted for youth with disabilities. The mall is an important gathering place where adolescents often socialise and develop community living skills, yet participation may be restricted. The aim of this study was to evaluate the facilitators and barriers to participation in a shopping mall through the perspectives of adolescents with disabilities. Method: Semi-structured individual interviews were conducted with adolescents aged 12–19 years with a physical and/or sensory disability. Audio recordings were transcribed verbatim and coded following a template analysis using the International Classification of Functioning Disability and Health (ICF). Results: Eleven youth (six females, mean age = 17.0 years) participated. Medical conditions included visual impairment, hearing impairment, cerebral palsy, hemiplegia, osteogenesis imperfecta and congenital amputations. Six themes were identified by the adolescents: what the shopping mall means to me, physical environment, transportation, social factors, attitudes and the person. The majority of themes mapped to the ICF's 'environmental factors'. Conclusions: Facilitators and barriers identified were either generic or disability-specific, implying that some modifications to shopping malls may be beneficial across disability types. Changes made to the physical, social and attitudinal environment are required to enable full participation of youth with disabilities within a shopping mall and other built environments of high public access. Implications for Rehabilitation: The meaning of the shopping mall according to youth with disabilities includes socialisation, shopping, getting out of the home and employment. The majority of themes mapped to 'environmental factors' indicating that most obstacles to participation are caused by environmental barriers. Facilitators and barriers identified were either generic or disability-specific implying that some modifications to shopping malls may be beneficial across disability types. Changes made to the physical, social and attitudinal environment are required to enable full participation of youth with disabilities within a shopping mall.